He-Ne Laser Irradiation Encourages reparative processes After cartilage loss in New Zealand rabbits (Baghdad Science Journal, 2008)
Many therapeutic methods used to encourage reparative processes of cartilage and accelerate their healing such as drugs, magneto-laser and so on. Twenty four adult New Zealand rabbits used in this study. They were divided in to two groups; control and treaded with He –Ne laser. A square skin flap done on the medial aspect of both auricles followed by pealing a square piece of cartilage from the auricle then the flaps sutured .The site of the operation in the rabbits of the treated group were irradiated with He –Ne laser 5mw power for seven days began after the operation directly. 3 rabbits from each group used for collection of specimens for histopathological examination at the 1, 2, 4 & 6 weeks post the operation. Significantly well developed cartilage growth, chondroblasts and chondrocytes invade the area of the operation .High increase in the thickness of connective tissue in the same area contain mainly collagen fibers and lesser amount of elastic fibers. He –Ne laser irradiation raised the mitotic activity of the cartilage cells, activated the reproduction processes in addition to the intra and extra regenerative repair